Frailty Predicts Poor Prognosis of Patients After Percutaneous Coronary Intervention: A Meta-Analysis of Cohort Studies - Wang, Peng; Zhang, Shutang; Zhang, Ke; Tian, Jie (Frontiers in Medicine, 2021)
Background: Frailty has been related to a higher risk of cardiovascular events, while the association between frailty and outcomes for patients with coronary artery disease (CAD) after percutaneous coronary intervention (PCI) remains unclear. We performed a meta-analysis of cohort studies to evaluate the above association. Methods: Cohort studies aiming to determine the potential independent association between frailty and clinical outcomes after PCI were identified by search of PubMed, Embase, and Web of Science databases from inception to February 22, 2021. A random-effects model that incorporates the possible heterogeneity among the included studies was used to combine the results. Results: Ten cohort studies with 7,449,001 patients were included. Pooled results showed that frailty was independently associated with higher incidence of all-cause mortality (adjusted risk ratio [RR] = 2.94, 95% confidence intervals [CI]: 1.90 to 4.56, I2 = 56%, P < 0.001) and major adverse cardiovascular events ([MACEs], adjusted RR = 2.11, 95% CI: 1.32 to 3.66, I2 = 0%, P = 0.002). Sensitivity analyses limited to studies including elderly patients showed consistent results (mortality: RR = 2.27, 95% CI: 1.51 to 3.41, I2 = 23%, P < 0.001; MACEs: RR = 2.44, 95% CI: 1.44 to 4.31, I2 = 0%, P = 0.001). Subgroup analyses showed that characteristics of study design, follow-up duration, or type of PCI did not seem to significantly affect the associations (P values for subgroup analyses all > 0.05). Conclusions: Frailty may be an independent risk factor of poor prognosis for patients with CAD after PCI.